2011
DOI: 10.1680/geot.9.p.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grading on the mechanical behaviour of Stava tailings

Abstract: Tailings dams can be fragile structures and too often they are subject to liquefaction. The material they are composed of is rather peculiar, having a man-made origin, and their behaviour is still not very well understood. The soil from the Stava tailings dams, structures that were subject to liquefaction in 1985 causing extensive destruction, was investigated in this study as an example of tailings. Two main aspects of their behaviour have been examined: the influence of the percentage of silt and sand that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
6
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(123 citation statements)
references
References 27 publications
8
107
6
2
Order By: Relevance
“…The value of stress ratio at the critical state, (q/p') cs , has been predicted from the stress-dilatancy graph (Fig. A1(b)) for the test, extending the last part of the curve to the point of intersection with the zero dilatancy axis (Carrera et al 2011). The rate of volumetric strain, δε v /δε s , plotted against the stress ratio was used to assess dilatancy, where ε v is volumetric strain and ε s is deviatoric strain.…”
Section: Appendix A: Example Of Estimation Of Critical Statementioning
confidence: 93%
See 1 more Smart Citation
“…The value of stress ratio at the critical state, (q/p') cs , has been predicted from the stress-dilatancy graph (Fig. A1(b)) for the test, extending the last part of the curve to the point of intersection with the zero dilatancy axis (Carrera et al 2011). The rate of volumetric strain, δε v /δε s , plotted against the stress ratio was used to assess dilatancy, where ε v is volumetric strain and ε s is deviatoric strain.…”
Section: Appendix A: Example Of Estimation Of Critical Statementioning
confidence: 93%
“…The pre-shear void ratios (e i ) for the ballast specimens have been determined from weight-volume relationships and been summarised in Table 2. The critical state was determined by extrapolation of stress-strain data to a most probable value following an approach recommended by Carrera et al (2011). The BBI values calculated by eq.…”
Section: Model Validationmentioning
confidence: 99%
“…plane. As theˆnes content increases and the soil becomes better graded, many have found that the critical state line moves downwards (e.g., Fourie and Papageorgiou, 2001) and some have seen that as theˆnes content is increased further, it then starts to move back upwards (e.g., Thevanayagam et al, 2002;Murthy et al, 2007;Carrera et al, 2011). In these examples, the predominant movement in the critical state line was a vertical translation, whereas in other cases, signiˆcant changes of gradient have been seen with less pronounced translation (e.g., Coop and Atkinson, 1993;Andrianopoulos et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For the specimens prepared at RC level of 90% and tested at high effective confining pressures that did not reached critical state at axial strains of 35%, an extrapolation method proposed by Carrera et al (2011) was adopted to estimate the location of critical state.…”
Section: Stress-strain Behaviour and Associated Breakagementioning
confidence: 99%